Active and Passive Smoking as Catalysts for Cognitive Impairment in Rural Indonesia: A Population-based Study - Faizal Muhammad; Afifah Syifaul Ummah; Farida Aisyah; Rivan Danuaji; Diah Kurnia Mirawati; Subandi Subandi; Baarid Luqman Hamidi; Ervina Arta Jayanti Hutabarat; Reviono Reviono; Yulie Erida Nur Rahmawati; Isa Ridwan (Oman Medical Journal)
Objectives: Research indicates that active smokers are at risk of cognitive impairment. However, the correlation between chronic passive smoking and the risk of cognitive impairment remains underexplored. This study aimed to determine the association between smoking, passive smoking, and cognitive impairment and examined the dose-response effect. Methods: This population-based two-year survey was conducted in four rural public health centers from 2021 to 2023 in Central Java, Indonesia, each center caters to approximately 30 000 people. The participants were selected using simple random sampling from the health center visitors aged 30–60 years. Smoking and passive smoking were determined by self-assessment. Mini-Mental State Examination was used to evaluate cognitive impairment. The potential impact of confounding variables such as lifestyle, sociodemographic factors, and chronic diseases were considered and excluded during statistical analysis. Results: The participants were 409 individuals aged 30–60 years. The majority were men (264; 64.5%). Among them, 308 (75.3%) were active smokers, 271 (66.3%) were passive smokers, and 138 (33.7%) were not exposed to tobacco smoke. There was a significant relationship between cognitive impairment and increasing pack years of active smoking. The highest and most significant risk was observed in those who smoked ≥ 20 pack-years with an adjusted odds ratio (aOR) of 1.61 and 95% CI: 0.98–2.31. Passive smokers had a slightly lower risk of cognitive impairment than those who did not smoke and never smoked (aOR = 2.01; 95% CI: 1.37–2.70). They were comparable with OR of 10–19 pack-years total exposure to active smoking (aOR = 1.86; 95% CI: 1.24–2.42). Conclusions: There was a dose-response relationship between smoking and cognitive impairment with a significant effect on ≥ 20 pack-years of exposure. Passive smoking also indicated a significant risk of cognitive impairment equivalent to an estimated 10–19 pack-years of active smoking.